Maternal Mortality: Findings from Verbal Autopsy of Maternal Deaths in District Multan (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To assess the existing magnitude of maternal mortality ratio (MMR) and factors contributing to maternal death. Methods: A cross- sectional descriptive study was carried out in Multan district with a total population of 1.3 million. The data on all maternal deaths and total number of live births in district Multan during the year 2004 were obtained from National program for family planning and health care. Family members, friends and relatives of the deceased mother were interviewed. A pre-tested questionnaire was used to collect information on demographics, circumstances of death, past obstetrical history, ante-natal natal and postnatal history of last pregnancy. Descriptive Analysis including descriptive statistics were performed. Results: A total of 28621 live births and 40 maternal deaths occurred in Multan district during the year 2004. The MMR of this study population was 140/100000. A higher proportion of women were illiterate, (65%) had poor socio-economic status, were primae gravida or multipara (72.5%) (more than 5 pregnancies) and had received poor ante-natal natal and post- natal care (61%). Most women were delivered by traditional birth attendants (TBAs) (55%), had excess bleeding especially postpartum hemorrhage (PPH), and faced problems during visit to the health facility. 27.5% died at home or on way to the hospitals. Conclusion: Provision for essential obstetric care (EOC) services in addition to the existing services will be essential to bring about a significant decline in maternal morbidity and mortality. The existing services alone are insufficient to achieve a reduction in maternal mortality.
Keywords: Verbal Autopsy, Maternal Mortality Ratio, Traditional Birth Attendants, Post-Partum Hemorrhage, Essential obstetric care services, comprehensive obstetric care services.